Kriteria Kelayakan Pos Observasi Bulan (POB) Rukyah Al-Hilal: Studi Kasus Gunung Sekekep Pulung Ponorogo - Muhammad Furqon Ahsani; Novi Fitia Maliha (Jurnal Antologi Hukum, 2021)
This research was motivated by the implementation of rukyatul hilal conducted by the Ministry of Religious Affairs of Ponorogo Regency. The BHR team of Ministry of Religious Affair in the field encountered several obstacles, namely the difficulty of seeing hilal due to natural factors. The goal in this study was to explain how the criteria of a place could be said to be feasible to look at hilal. There are various things related to the implementation of rukyat al-hilal that must be considered. This aims so that the implementation can run smoothly and can also successfully see the hilal. Because there are many factors that have been behind the absence of hilal. This research uses this type of field research. The approach used is quality. Based on the results of this research analysis resulted in findings, that carrying out hilal rukyatul activities must pay attention to various aspects of both infrastructure facilities and environmental conditions where to be used as lunar observation posts (POB). This is because not every place can be used to see hilal so there needs to be a review of every place that is expected to be possible to see hilal. Basically the place to see hilal must meet various eligibility criteria as a place for hilal rukyatul.